Robert Barclay and Kabbalah. Issue 1 (June 2016) - Birkel, Michael
Abstract : Robert Barclay inhabited a broad spiritual and theological cosmos. Long recognised as a Jesuit-trained ex-Calvinist well versed in Protestant scholastic theology, Barclay was also acquainted with Jewish Kabbalistic writings through Knorr von Rosenroth's Kabbala denudata . A comparison of Barclay with his friend George Keith, also influenced by von Rosenroth, reveals new layers of meaning in Barclay's work, particularly in applications of Kabbalistic terms to Christology.